Influence of tibial tuberosity position and trochlear depth on patellar tracking in patellar instability: Variations with Patella Alta. (July 2021) - Conry, Keegan T.; Cosgarea, Andrew J.; Tanaka, Miho J.; Elias, John J.
Abstract: Background: Patella alta reduces articular constraints acting on the patella from the trochlear groove with the knee extended. The current study was performed to address how patella alta alters the influence of tibial tuberosity position and trochlear depth on patellar tracking in patients being treated for patellar instability. Methods: Fifteen subjects with recurrent patellar instability participated in knee extension within a dynamic CT scanner. Computational models were reconstructed from the motions to characterize patellar lateral shift, patellar tilt, patellar height, trochlear depth and lateral position of the tibial tuberosity at 0° and 30° of knee flexion. Linear regressions were used to correlate patellar tracking with anatomy for an alta group (7 knees, Caton-Deschamps index > 1.2) and a non-alta group. Findings: For the alta group, lateral patellar shift and tilt increased with increasing lateral position of the tibial tuberosity at 0° (r 2 > 0.8, P < 0.005). For the non-alta group, lateral patellar shift and tilt increased as depth of the groove decreased at 0° (r 2 > 0.8, P = 0.001). Lateral patellar tilt also increased with increasing lateral position of the tibial tuberosity at 30° for the non-alta group (r 2 = 0.55, P = 0.04). Interpretation: For patients with patellar instability, lateral patellar maltracking with the knee extended can be largely attributed to either a shallow trochlear groove or a combination of patella alta and a lateral position of the tibial tuberosity. These relationships should be considered in both conservative and surgical treatment planning. Highlights: Patella alta influences patellar tracking near full extension. With alta, a lateral tibial tuberosity is correlated with patellar maltracking. Without alta, a shallow trochlear groove is correlated with patellar maltracking.EEE